1995
DOI: 10.1128/mcb.15.10.5598
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of Proteins to the Noncoding Strand of a Crucial Element of the Variant Surface Glycoprotein, Procyclin, and Ribosomal Promoters of Trypanosoma brucei

Abstract: The variant surface glycoprotein (VSG) and procyclin promoters of Trypanosoma brucei recruit an RNA polymerase sharing characteristics with polymerase I, but there is no sequence homology between them nor between these promoters and ribosomal promoters. We report the detailed characterization of the VSG promoter. The 70-bp region upstream of the transcription start site was sufficient for full promoter activity. Mutational analysis revealed three short critical stretches at positions ؊61 to ؊59 (box 1), ؊38 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
(75 reference statements)
0
37
0
Order By: Relevance
“…The very simple structure and ribosomal nature of the ES promoters (39,40) is in keeping with the absence of regulatory sequences. In support of this notion, promoters from active or inactive ESs share the same sensitivity to DNase (24), and antigenic variation still occurs properly if the promoter of the active ES is replaced by the ribosomal promoter (41,42). Other arguments include the detection of transcripts originating from inactive ESs such as RNA transcribed from the ES beginning in procyclic forms (29), RNA from antibiotic-resistance genes inserted in inactive ESs (25), or RNA from different ESAG6 from inactive ESs, accounting for up to 20% of the total ESAG6 transcripts (28).…”
Section: Discussionmentioning
confidence: 69%
“…The very simple structure and ribosomal nature of the ES promoters (39,40) is in keeping with the absence of regulatory sequences. In support of this notion, promoters from active or inactive ESs share the same sensitivity to DNase (24), and antigenic variation still occurs properly if the promoter of the active ES is replaced by the ribosomal promoter (41,42). Other arguments include the detection of transcripts originating from inactive ESs such as RNA transcribed from the ES beginning in procyclic forms (29), RNA from antibiotic-resistance genes inserted in inactive ESs (25), or RNA from different ESAG6 from inactive ESs, accounting for up to 20% of the total ESAG6 transcripts (28).…”
Section: Discussionmentioning
confidence: 69%
“…BES promoters, although highly conserved at the sequence level, require only two elements, boxes 1 and 2, for transcriptional activity (30,37). Both boxes are required to form a stable DNA-protein complex in electrophoretic mobility shift assays or to compete with a specific in vitro transcription signal (22,31), which suggests that they cooperate in the recruitment of trans-acting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Vanhamme and colleagues (37), by testing for putative box 2 activity in the possible 11.17 MVSG promoter, also showed that the region corresponding to Ϫ36 to Ϫ26 of the 1.63 MVSG promoter is essential. In terms of promoter activation, we believe that similarities to box 2 or box 1 might not be relevant.…”
Section: Vol 1 2002mentioning
confidence: 99%
“…In addition, another distinct factor binds to an upstream promoter element and activates ribosomal DNA (rDNA) transcription by stabilizing PIC formation. The VSG ES promoter extends only 67 bp upstream of the transcription initiation site and consists of two short sequence elements (24,34). Since both elements are required for efficient binding of purified CITFA (1) and since they are so close to the initiation site, CITFA appears to be the functional equivalent of the yeast core factor and human SL1.…”
Section: Discussionmentioning
confidence: 99%